Laboratory Data for Oil Recovery by Injecting Low-Salinity Water into Sandstone from Brazilian Campos Basin Reservoir - Beatriz Lemos; Alessandra Winter; Erika Blini; Nilo Kim; Rafael Almeida (Journal of Petroleum Science and Technology)
The enhanced oil recovery method by low-salinity water flooding in sandstones has had promising results. When two immiscible phases are in contact with a solid surface, one is generally more strongly attracted by the solid than the other, called the wetting phase. The ability of different polar compounds to change the rock wettability depends on the rock type. In sandstone reservoirs, the electrostatic attraction between the positively charged surface of the oil and the negatively charged basal plans of the rock controls the oil adhesion on the rock surface. It is well known that typically lowering the injection brine salinity can enhance oil recovery, however, the effects of low-salinity water injection in sandstones are probably the result of several mechanisms acting in conjunction, highlighting the need to execute experimental tests. Moreover, this study aimed to evaluate the effect of brines with different compositions and salinity on the oil recovery factor of reservoir sandstone cores by carrying out core flooding experiments. In addition, reservoir cores were very friable, so sandpacks were produced to facilitate manipulation and make it possible to carry out the water flooding tests. Furthermore, they were used in four core flooding tests. Also, results indicated a potential low-salinity water effect, with an average incremental oil recovery of around 5.8%. The injectivity was analyzed using differential pressure during the experiments, and significant alterations were not observed due to the change in salinity of injected brines. Ultimately, the mineralogical analysis suggests that even sandstones with no clay content might show additional oil recovery due to low-salinity water injection, bespeaking the need to conduct more experiments for further investigation of the impact of the injected brine, the mineralogical composition of the rocks and the acting mechanisms.